The Use of Three-Dimensional (3D) Biometric Measurements to Predict Additional Alignment Procedures in Total Ankle Replacement. Issue 2 (25th April 2019) - Netto, Cesar de Cesar; Roberts, Lauren; Fansa, Ashraf; Newcomer, Meghan; Saito, Guilherme; Deland, Jonathan; Ellis, Scott; Demetracopoulos, Constantine
Category: Ankle Arthritis Introduction/Purpose: Preoperative evaluation of ankle and hindfoot deformities in patients undergoing total ankle replacement (TAR) is challenging. Characterizing deformity based on conventional radiographs is limited by its two-dimensional (2D) nature and is influenced by anatomical and operator-related bias. The final decision to perform associated corrective alignment procedures, that include calcaneal osteotomies, midfoot and forefoot osteotomies/fusions, and soft tissue balancing, is made intraoperatively following insertion of the TAR components. The use of weightbearing cone beam CT (WB CBCT) images and three-dimensional (3D) biometric tools, encompassing the hindfoot alignment, foot tripod, and center of the ankle joint, may be an effective surgical planning instrument. In this retrospective study, we assessed the ability of these tools to predict additional procedures performed at the time of TAR. Methods: In this retrospective study, we enrolled 22 patients that underwent TAR and had preoperative WB CBCT studies. We excluded seven patients with isolated ankle CBCT images and three with metallic hindfoot implants. Patients demographics, type and number of additional alignment procedures were noted. The WB CBCT data sets were screened using built-in semi-automatic measurement software. 3D coordinates (x/y/z) were identified for the specific anatomical landmarks required to calculate Foot and Ankle Offset (FAO), which included the WB points of the first, fifth metatarsal heads and calcaneus, as well as the highest point of the talar dome. FAO is a representation of the torque (offset) between the hindfoot/forefoot midline and the center of the talus, and is given as a percentage of foot-length. Patients were then divided into varus and valgus hindfoot alignment groups accordingly to their measured FAO, using available literature FAO values for normally aligned feet (2.3%, ±2.9%). Results: We included 12 patients (6F/6 M), mean age 65 (range, 47-80). The mean preoperative FAO was 5.73 (CI -0.99 - 12.55). Seven patients had valgus and 5 patients had varus alignment of the hindfoot. The mean number of additional procedures was 2 (range, 0 to 5), and included: calcaneal osteotomy (58%), Achilles lengthening/Gastroc recession (58%), Cotton osteotomy (25%), First TMT fusion (17%), talonavicular fusion, naviculo-cuneiform fusion, and Brostrom procedure (8%). The FAO positively correlated with occurrence of additional alignment procedures (p=0.003). Patients with valgus hindfoot alignment had significantly increased number of additional procedures (2.7; CI 1.6 – 3.8) when compared to varus alignment patients (1.2; CI -0.1 – 2.5) (p=0.03), and were found to have a 1.8 fold greater chance to have a calcaneal osteotomy. Conclusion: This is the first study to evaluate the role of 3D biometric tools and semi-automatic WB CBCT measurements in the preoperative assessment of foot alignment in patients undergoing TAR. We found that increased Foot and Ankle Offset (FAO) significantly predicts the occurrence and number of additional alignment procedures, including calcaneal osteotomies. We believe that the use of biometrics and semi-automatic measurements, which account for the relationship between the center of the ankle and the tripod of the foot, can enhance the preoperative assessment, surgical planning and outcomes of TAR patients. Prospective and postoperative studies demonstrating correction are needed.